Public awareness regarding the manufacturer provided information about medicine usage, safety, and adverse drug reactions in Balochistan, Pakistan - Khan, Gullab; Haq, Noman; Ahmad, Nafees; Nasim, Aqeel; Javaid, Asma; Saood, Mujhammad; Yasmin, Riffat; Tahir, Maria; Riaz, Sohail; Danish, Zeeshan; Razzaq, Ghulam; Khan, Abdullah; et al. (Frontiers in Pharmacology, 2023)
Objectives This study aimed to analyze the general public's awareness of medicine information, safety, and adverse drug reactions in Quetta, Pakistan. Methods A cross-sectional descriptive study was conducted using random sampling from April 2020 to April 2021 in Quetta. Samples were collected from respondents who met the inclusion criteria and had visited community pharmacies. The analysis was done using SPSS version 23. Bivariate and multivariate analyses were performed to assess factors associated with good knowledge. Results Multivariate analysis revealed that purchase on prescription was a determining factor of knowledge regarding knowledge of pharmaceutical products and their provided information, medicines usage and safety, and Medication ADRs. Patients who bought medicines on prescriptions were more likely to have better knowledge. Patients having education were more likely to have better knowledge. Conclusion Public awareness about medicine information, safety, and the information provided by manufacturers is crucial to ensuring that patients have access to accurate information about their medications and can make informed decisions about their health. Healthcare providers and regulatory bodies must work together to improve access to information and promote safe medication practices. Keywords: Public Awareness, Medicine Information, Safety, Quetta, Pakistan